Acute stress response of fathead minnows caged downstream of municipal wastewater treatment plants in the Bow River, Calgary. - Analisa Lazaro-Côté; Bastien Sadoul; Leland J Jackson; Mathilakath M Vijayan (PLoS ONE)
We examined whether exposure to municipal wastewater effluent (MWWE) compromised the stress performance of laboratory-reared fathead minnows (Pimephales promelas) in a field setting. Adult minnows were caged at two sites upstream and three sites downstream of wastewater treatments plants (WWTPs) discharging MWWE into the Bow River, Calgary, Alberta, Canada. At each site one group of fish was sampled after a 26 day exposure to MWWE, while another group was subjected to 1-min air exposure followed by 60-min confinement and then sampled. Fish morphometrics and proximate composition were measured, and whole-body cortisol, glucose and lactate levels assessed as markers of the stress response. The whole-body protein, glycogen and lipid content were higher at the site closest to a WWTP outfall relative to the other downstream and upstream sites. There were no significant differences in whole-body cortisol levels in minnows sampled at sites either upstream or downstream of WWTPs. Acute stressor exposure significantly elevated whole-body cortisol levels in all groups, and this response was not modified by the location of the sampling sites. The whole-body metabolite profile, including glucose and lactate levels, were significantly higher in fish caged immediately downstream from WWTP inputs relative to upstream sites. There was an acute-stressor-mediated increase in whole-body lactate, but not glucose, levels and this response was independent of sampling site. The results reveal that the capacity to evoke an acute stress response was not compromised in fathead minnows caged for 26 days downstream of WWTPs in the Bow River. However, there were changes in the whole-body proximate composition and metabolite levels immediately downstream from the WWTP outfall suggesting greater accumulation of energy stores in these fish. Taken together, our results suggest that environmental factors in addition to contaminants, including higher water temperature and nutrient availability, influence the impact of MWWEs on fish stress performance.